Effect of diets containing fish oil and different levels of purslane meal on production performance and carcass quality of broiler chickens. (October 2019) - Kartikasari, L R; Hertanto, B S; Putra, S M; Iswara, Y; Nuhriawangsa, A M P
Abstract: The aim of the study was to investigate the effect of dietary inclusion of purslane meal ( Portulaca oleraceae ) and sardines fish oil as a source of omega-3 fats on production performance and carcass quality of broiler chickens. A total of 180 one-day old unsexed Cobb broiler chickens were used in this study. The broilers were randomly allocated into 30 pens with each pen consisted of 6 birds. The pens were randomly assigned to five dietary treatments with 6 replicates (36 birds per treatment). The diets were prepared from a basal diet (P0). The experimental diets were formulated by supplementing the basal diet containing 1.5% sardines fish oil and levels of purslane meal 0 (P1), 6 (P2), 12 (P3), and 18.0% (P4). Water and diets were provided ad libitum for a period of 35 days. Data production parameters were recorded weekly. The data were analysed using analysis of variance (ANOVA). Differences between treatment means were further analysed using Duncan's New Multiple Range Test. Results showed that there were no significant effects on production parameters and carcass weight by adding of dietary purslane meal up to a level of 12%. However, supplementation of 18% purslane meal (P4) resulted in a decrease in body weight from 1718 g (P0) to 1278 g (P4) and in carcass weight from 1139 g (P0) to 811.5 g (P4). It was concluded that dietary levels of purslane meal up to a level of 12% didn't have negative effect on production performance and carcass quality of broiler chickens.